Broadening energy access for poor households in rural malawi: How pico solar, mobile money, and cloud-based services are being combined to address energy exclusion - Walwyn, David R.; Hanlin, Rebecca (Frontiers in Energy Research, 2022)
Solar lighting has become the primary lighting source for households within rural Malawi, where many households remain off-grid and unable to afford the purchase of large, independent power systems. However, this success has not been without its challenges. The paradox is that, historically, even the lowest cost systems require an initial investment beyond the means of low-income households, and hence necessitate the use of expensive and exploitative financing options, such as those offered by micro-finance institutions. In this study, we explore in a case study how one solar company, Yellow, has overcome this structural inequity by combining three low-cost technologies, namely Pay-As-You-Go, mobile money (MoMo) and cloud-based services (XaaS), to develop a novel platform, referred to as Ofeefee, which is able to deliver product into a market characterised by a weak retail infrastructure and low purchasing power. The result is a better quality lighting at a lower levelised cost than the traditional technologies. The research suggests that credit and retail systems in low income areas may be transformed by the emergent technologies of MoMo and XaaS. This trend has implications for both market formation and employment within these areas.